Institutional Betrayal: Who Is Most Vulnerable? - Pinciotti, Caitlin M. (Journal of interpersonal violence, 2021)
Institutional betrayal occurs when, following sexual victimization, institutions create hostile environments which normalize sexual violence, make it difficult to report the experience, mishandle the complaint, attempt to cover up the experience, or retaliate against survivors. These responses are not uncommon and have been linked to adverse survivor outcomes such as dissociation, anxiety, sexual dysfunction, poorer physical health, and depression, yet little is known about which survivors are most at risk for experiencing institutional betrayal. Using a sample of 404 sexual assault survivors recruited from Amazon Mechanical Turk, the current study employed logistic regression to identify risk factors for institutional betrayal. The findings indicate that institutional betrayal is more likely to be reported by survivors who identify as heterosexual, were older at the time of the assault, and endorse more severe PTSD symptoms yet, unexpectedly, less severe distress severity. Gender, race, assault characteristics, and disclosure tendencies did not significantly predict institutional betrayal risk. Although some relationships may be bidirectional, the results suggest that survivors already at risk for some negative post-assault outcomes may be particularly at risk for institutional betrayal.